Death at Holly Lodge - Innes, Louise R. (Innes, Louise R. Daisy Thorne mystery., 2021)
"Ooh La La hair salon owner Daisy Thorne adores the Christmas cheer in her picturesque hometown of Edgemead, England. Excitement is extra high this year, as international pop star Mimi Levanté, the village's newest resident, begins renovating historic Holly Lodge. But the charming country home's makover is cut short by a shocking discovery--the body of a man, dressed as Santa Claus, jammed inside the house's chimney! The secreted Santa is identified as Thom Pierce, a local father who vanished on Christmas Eve two years ago. As the case moves from missing to murder, Daisy and dashing DCI Paul McGuinness begin combing through the clues of Christmases past. But the killer will go to great lengths to keep old crimes under wraps. Now, DCI McGuinness must protect Daisy as she tries to untangle the mystery before a merry murderer embarks on another slay ride." -- back cover.